Fate and Growth Kinetics of Salmonella and Listeria monocytogenes on Mangoes During Storage - Saha, Joyjit; Topalcengiz, Zeynal; Sharma, Vijendra; Friedrich, Loretta M.; Danyluk, Michelle D. (Elsevier, 2023)
Imported mangoes have been linked to outbreaks of salmonellosis in the USA. The purpose of this research was to evaluate the persistence and growth kinetics of Salmonella and Listeria monocytogenes on the intact surface of whole 'Ataulfo', 'Kent', and 'Tommy Atkins' mangoes stored at three different temperatures. L. monocytogenes was also evaluated on fresh-cut 'Tommy Atkins' mangoes stored at 4, 12, 20 +/- 2 degrees C. Whole mangoes were spot inoculated with rifampicin-resistant pathogen cocktails (6 log CFU/mango) onto the midsection of whole fruit (n = 6). Fruit was stored at 12, 20, or 30 +/- 2 degrees C and sampled for up to 28 days. The specific growth rates derived from DMFit models as a function of time were used to develop secondary models. On 'Kent' mangoes, Salmonella had a population increase from 0.3 to 1.1 log CFU/mango with a linear growth rate of similar to 0.004, 0.01, and 0.06 log CFU/mango/h at 12, 20, and 30 degrees C, respectively. At 20 and 30 degrees C, Salmonella growth rates were significantly higher than 12 degrees C (P < 0.05). No clear Salmonella growth trend was observed; populations decreased up to 1.6 log CFU/mango on 'Tommy Atkins' and 'Ataulfo' at 12 degrees C. Populations of L. monocytogenes on whole and fresh-cut mangoes declined regardless of temperature and storage period. Food safety during storage should be the top priority for fresh-cut tropical fruit processors.
Keywords: Dmfit; Fresh Cut; Growth Rates; Modeling; Survival; Whole Mangoes; Escherichia-Coli O157h7; Multistate Outbreak; Fresh; Cantaloupe; Survival; Internalization; Consumption; Pathogens; Surfaces; Honeydew